KELIMPAHAN DAN POLA SEBARAN REMIS Donax sp. DI PANTAI BATU BEDAUN DAN PANTAI BERIGA BANGKA BELITUNG - Umroh Umroh; Suarman Suarman; Kurniawan Kurniawan (Journal of Aquatropica Asia, 2019)
Research to find out the abundance and distribution pattern of Bean Calms (Donax sp) at Batu Bedaun Beach and Beriga Beach at Province of Bangka Belitung Island in March 2017. Determination of sampling location was done by Purposive Random Sampling method. Sampling was done at 2 locations and each of 3 stations with 4 replications. Physical and chemical parameters measured include: temperature, salinity, humidity, pH, substrate base of waters, while the measurement of the bottom substrate of the waters was conducted in the Water Resource Management Laboratory, Faculty of (Agriculture, Fisheries and Biology) University of Bangka Belitung. The results showed that the population abundance of Bean Calms (Donax sp) in Batu Beach Bedaun of Sungailiat Subdistrict ranged between 6 ind/m2 - 16 ind/m2. Abundance analysis in general shows low abundance, whereas in Pantai Beriga Kecamatan Lubuk Besar ranges between 151 ind/m2 - 194 ind/m2 and abundance in general shows high enough abundance. Morisita index analysis in general shows the pattern of distribution of Bean Calms (Donax sp) in Batu Bedaun Beach, Sungailiat Subdistrict, including uneven category (Id<1), whereas in Beriga Beach Lubuk Besar Subdistrict is classified as (Id>1).